Coherent State Quantization of Time of Arrival Functions of Confined and Free Particles - Romeo, Daisy A (Archīum Ateneo, 2022)
This work presents coherent state quantization f↔f(x)|XX|dμ(X) applied to the classical time of arrival functions of the form T(q,p)=-μqp, expressed in different coordinate systems, corresponding to phase spaces of the p confined and free particle, respectively. The most important ingredient in this technique is the coherent state. Two ways of constructing coherent states will be adopted:via unitary group representations and via superposition method, applied to time of arrival function of one-dimensional confined and free particles.